2003
DOI: 10.1136/bmj.326.7390.649
|View full text |Cite
|
Sign up to set email alerts
|

Medicine, management, and modernisation: a "danse macabre"?

Abstract: To break their destructive antagonism over issues of health service modernisation, doctors and managers should engage more directly with nursing and allied health professionals when responding to reform initiatives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
162
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(174 citation statements)
references
References 10 publications
(9 reference statements)
8
162
1
1
Order By: Relevance
“…However, since the 1970s such idealised conceptions of professionalism and professional autonomy have been tempered and critiqued (Atkinson, Reid, & Sheldrake, 1977;Kennedy, 1981;Larson, 1977). The medical profession has been the subject of renewed attention since the 1990s when governments in many developed Manuscript Click here to view linked References 2 countries, notably the United Kingdom and United States, attempted to strengthen managerial and bureaucratic control over doctors within state and insurance funded health systems (Alaszewski, 1995;Degeling, Maxwell, Kennedy, & Coyle, 2003;Harrison & Ahmad, 2000;Harrison & Pollitt, 1994). Further challenges to doctors' professional autonomy followed in wake of the rising evidence based medicine movement that targeted the mystique and privacy of medical decisionmaking (Greenhalgh, 1996;Horton, 1995;Smith, 1991), and new formalised systems of patient management, such as care pathways, provided an increased clinical impetus for interprofessional collaboration (Pinder, Petchey, Shaw, & Carter, 2005).…”
mentioning
confidence: 99%
“…However, since the 1970s such idealised conceptions of professionalism and professional autonomy have been tempered and critiqued (Atkinson, Reid, & Sheldrake, 1977;Kennedy, 1981;Larson, 1977). The medical profession has been the subject of renewed attention since the 1990s when governments in many developed Manuscript Click here to view linked References 2 countries, notably the United Kingdom and United States, attempted to strengthen managerial and bureaucratic control over doctors within state and insurance funded health systems (Alaszewski, 1995;Degeling, Maxwell, Kennedy, & Coyle, 2003;Harrison & Ahmad, 2000;Harrison & Pollitt, 1994). Further challenges to doctors' professional autonomy followed in wake of the rising evidence based medicine movement that targeted the mystique and privacy of medical decisionmaking (Greenhalgh, 1996;Horton, 1995;Smith, 1991), and new formalised systems of patient management, such as care pathways, provided an increased clinical impetus for interprofessional collaboration (Pinder, Petchey, Shaw, & Carter, 2005).…”
mentioning
confidence: 99%
“…[9][10][11][12] Although one panacea would include a more egalitarian professionalism, 3,10, 13 Degeling et al have argued that doctors' individualistic attitudes to their work make them less supportive of teamwork than nursing colleagues and managers. 1 Such underlying tensions have not been widely examined in maternity settings, yet lively public controversies about the appropriate "social design" of birth impact directly on organisational and professional arrangements. 14,15 As midwives have sought enhanced professional status, the relationship between midwifery and nursing has become contentious and the role boundaries between midwifery and obstetrics increasingly disputed.…”
mentioning
confidence: 99%
“…We wouldn't go as far as Degeling et al, 6 who suggested that some doctors were 'equivocal about financial realism'. However, it is hard to imagine the sheer amount of change management, information management, strategic management, and financial management that is necessary for the running of the NHS, being able to succeed without professional managers having a central role.…”
Section: Why This Matters To Usmentioning
confidence: 99%